Antarctica - Oachs, Emily Rose (Minneapolis, MN : Bellwether Media, 2016)
Introduces beginning readers to the continent of Antarctica. Includes glossary.
Includes bibliographical references (page 23) and index.
3.0
K-3
Keywords: Antarctica; Antarctica -- Geography; Antarctica; Antarctica -- Geography